AMCSKUK®: Aluminium Matrix Composite from AL SCRAP and Short Fibre-Alumina - Mohd Nazree Derman, Dr. (School of Materials Engineering, 2008)
Ekspo ini berlangsung di Dewan Sek. Men. Putra, Kangar, Perlis.